The duration of sleep in adolescent student in Denpasar (Annals of Medical Research, 2021)
Aim: To determine the duration of sleep of adolescents in high school in Denpasar. Material and Methods: A cross-sectional descriptive study, using a randomized sampling technique Performed in high school in Denpasar by the questionnaire-based survey. The inclusion criteria are adolescents of high school-aged 12-18 years agreed and signed a letter of approval as the subject of the study. Samples with medical disorders, psychiatric disorder, neurological disorders excluded. Research variables included: 1. Teen sleep duration in one day; 2. Variety of activities carried out by the subject both in & out school; 3. Sports habits; 4. Body Mass Index. Retrieving Data with the Pittsburgh Sleep Quality Index (PSQI), the Hamilton Halt Rating Scale (HARS) depression scale, obtained from the questionnaire the value of sleep duration and sleep quality index. Data were processed using SPSS 22. Results: 183 samples and 18 samples excluded because of medical illness. As many as 59.3% of women, the average age of 16.04 years, of which 54.5% sleep duration 8 hours with an average of 6-6.5 hours per day and started to sleep at 23.00 and 24.00, BMI 61,8% normal. The regular event of the subject is 1.72 hours per day outside the routine learning activities in the classroom, with the highest number of hours of exercise each day is 3 hours. Conclusion: The average sleep duration of adolescents in high schools in Denpasar is lacking and tends to prefer to sleep late at night.
Keywords: Duration of sleep; lacking; adolescents; high school.